Chinese Bonek: Reject Racism Through Symbolic Communication - Mas Yongky Satria Muhammad Purnomo; Nanang Krisdinanto (Kanal: Jurnal Ilmu Komunikasi, 2020)
This research starts from the phenomenon of the existence of Chinese Bonek (support- ers of the Persebaya Surabaya club who are of Chinese ethnicity) in the city of Surabaya. Although a minority in numbers (compared to Bonek ethnic or Javanese), the existence of Bonek Tionghoa began to be recognized among Bonek. Moreover, they also rou- tinely physically present at the stadium every time Persebaya competed. This study aims to unravel the experiences of the Chinese Bonek in supporting Persebaya, as well as understanding how they interpret that support. That experience is seen through verbal and non-verbal communication that they do, which of course implicitly has its own mean- ing and message. This research uses a qualitative approach, descriptive type, and uses the phenomenological method. Data obtained from in-depth interviews, supported by observation on the field (especially when Persebaya competed in the stadium). The find- ings of this research data show, Chinese Bonek apparently means that their support is not only as support for their favorite football club, but also as an expression of rejection of racism and discrimination that they often experience, both in daily life and in the context of the interaction of fellow supporters. The support is done through verbal communication such as singing (chant) and status or posting on social media, and through non-verbal communication such as direct attendance at the stadium, wearing a Persebaya jersey / costume, and certain gestures.